Design of a Solar Charger for Electric Vehicles (International Journal of Innovative Research in Engineering & Management, 2021)
The current global trend towards electric vehicles is growing as  governments and automobile manufacturers are focusing on  agendas such as “going green”, fighting climate change etc. The  electric vehicle design is a core part for these. The Electric vehicles  themselves run on electrical energy derived from an energy source,  commonly batteries. These batteries need to be charged. For this  purpose, a charging station needs to be provided. The charging  stations or points convert the energy available to them through various sources to electrical energy in DC form for the vehicle.  These chargers have to be able to accept user input, such as the  amount of power to be delivered, such that the user can pay for as  per requirement. In this paper a solar charging station with a local  battery reserve is simulated for charging of an electric vehicle. This  simulation lays the ground work for solar based designs for  Electric Vehicle (EV) chargers.
Keywords: Feedback; Boost Converter; MPP; Solar Array